2005
DOI: 10.1177/0734242x05060966
|View full text |Cite
|
Sign up to set email alerts
|

A critical review of economic valuation studies of externalities from incineration and landfilling

Abstract: The primary objective of this study was to assist waste management researchers, decision-makers and waste managers at national, regional and local levels, in their decision-making processes, with most recent valuations on the environmental and social costs of externalities associated with various pollutants and disamenities related to landfilling and incineration of municipal solid waste. The aim was achieved by mapping, gathering, analysing, comparing and synthesizing various valuation estimates, based on a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 18 publications
1
26
0
5
Order By: Relevance
“…Calculations of ϕ 1 and ϕ 2 —the compost‐production cost parameters—were from Pluda (2002), based on the windrow‐composting method, which is known to be cheaper than the alternative techniques of anaerobic digestion and in‐vessel composting (Karagiannidis and Perkoulidis, 2009; Komilis and Ham, 2004). The variable cost, ϕ 2 , includes external cost associated with N 2 O emissions, in terms of effective greenhouse gas, which is equal to the emission of 11 g per ton (Avnimelech et al, 2005) multiplied by the damage of $11.2/kg N 2 O (Eshet et al, 2005); this amounts to $0.12 per ton of compost. Compost application costs, ψ, and all other non‐compost‐related costs, ω m , were taken from sample cost calculations reported by IMARD (2008).…”
Section: Datamentioning
confidence: 99%
“…Calculations of ϕ 1 and ϕ 2 —the compost‐production cost parameters—were from Pluda (2002), based on the windrow‐composting method, which is known to be cheaper than the alternative techniques of anaerobic digestion and in‐vessel composting (Karagiannidis and Perkoulidis, 2009; Komilis and Ham, 2004). The variable cost, ϕ 2 , includes external cost associated with N 2 O emissions, in terms of effective greenhouse gas, which is equal to the emission of 11 g per ton (Avnimelech et al, 2005) multiplied by the damage of $11.2/kg N 2 O (Eshet et al, 2005); this amounts to $0.12 per ton of compost. Compost application costs, ψ, and all other non‐compost‐related costs, ω m , were taken from sample cost calculations reported by IMARD (2008).…”
Section: Datamentioning
confidence: 99%
“…The external costs of incineration are primarily found in the air pollution created by the garbage incinerated, and it is assumed that these are the only variable external costs. A review by Eshet et al (2005) summarizes the external costs found in the literature on waste incineration. This range of estimates summarizes a variety of measurement estimation techniques for a variety of demographic and geographic locations.…”
Section: Social and Municipal Welfare Implicationsmentioning
confidence: 99%
“…Parmi les travaux de synthèse aboutissant à une monétarisation d'impacts environnementaux, on peut citer : -Eshet et autres auteurs de l'université de Haïfa [2], qui passent en revue les résultats d'une douzaine d'études menées dans le monde depuis 1990 ; -pour la Commission européenne (DG Environnement), les rapports ExternE [3], ETSU [4], Coopers-Lybrand, CSERGE et EFTEC [5], ERM [6], COWI [7] et Eunomia [8] ; -pour le ministère britannique de l'Environnement (DoE, DEFRA), d'autres rapports de CSERGE, EFTEC et Warren Spring Laboratory [9] et de Coopers-Lybrand [10], ainsi que la synthèse de Davies et Doble [11], qui travaillent dans ce ministère ; -en France, l'étude du CEMAGREF pour l'ADEME [12] COWI [7], sur la base de diverses études, affiche une fourchette large, allant de 1 à 23 € par tonne de déchets municipaux mis en décharge. …”
Section: Bibliographie Et Résultatsunclassified